PAS Dilemmas in The Era of Abdul Hadi Awang - Sopi, Saiyid Radzuwan Syed; Jaafar, Faridah (2018)
The objective of this research is to identify the position of Parti Islam Se-Malaysia (PAS) as a party during their muktamar (general assembly) on June 6 in Kuala Selangor. PAS leadership has been dominated by ulama leaders, labelled ‘traditionalist’ or ‘purist’ and the ‘mainstreamer’ or ‘reformist’ had admit that they have lost their positions in the party. The focus of this research is to identify that when Hadi had successfully purged the reformist from being a part of the party members, he and his factions had made an unpredictable action to withdraw from multi-ethnic opposition coalition Pakatan Rakyat (PR) in June 16, 2015. As a result, PR was dissolved and the rift worsened after the PAS leadership was captured by conservatives and the party accepted a motion by its conservative ulama (clerics) wing to sever ties with the Democratic Action Party (DAP) and People Justice Party (PKR). Hadi realized that it is near impossible for PAS to be in power on the national level without assistance from the opposition parties. However, this research found that although Hadi was a veteran politician, he asserted that his ideology, characterized, political thought and the way he solved the political problem are against PH. Hadi was categorized as an arrogant person, often disagrees with his colleagues, lacking of coalition spirit and always making controversial statements toward PH.